The Effect of the Process-based Writing Approach on Writing Success and Anxiety of Pre-service Teachers - Arici, Ali Fuat; Kaldirim, Abdullah (KAMLA-RAJ ENTERPRISES, 2015)
The instruction of writing should start from childhood, and students' writing should be observed to increase their writing abilities. Furthermore, revealing writing mistakes and making studies according to these mistakes can contribute to developing these students' writing abilities. In this study, a quasi-experimental study method was proffered that tests the impact of the process-based writing approach on the writing skills of pre-service teachers. Therefore, the research was designed with a pretest/post-test control group of quasi-experimental design. For related samples, t-testing for independent samples and ANCOVA analysis were used, and the results were evaluated. In the results, writing instruction courses, in which Turkish pre-service teachers used activities in the scope of the process-based writing approach, were found to have a great impact on the written expression skills of Turkish pre-service teachers in the experimental group compared to those in the control group.
Keywords: Process-based Writing; Pre-service Teachers; Writing Skills; Writing Anxiety; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics